1991
DOI: 10.1111/j.1365-2826.1991.tb00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Chromogranin A and Chromogranin B (Secretogranin I) Synthesis in Bovine Cultured Chromaffin Cells

Abstract: in the present study we investigated the regulation of chromogranin A (CGA) and chromogranin B (CGB) biosynthesis in bovine shromaffin cells maintained in primary culture. Cellular proteins were labelled with [35S]methionine and the incorporated radioactivity was used as an index of the s y n t h e s i s rate. The radioactivity incorporated into CGA was determined by immunoprecipitation, m d that into CGB was quantified by a dot immunobinding assay using specific antibodies. Incubation of cells with carbamylch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
2

Year Published

1993
1993
2004
2004

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
2
13
2
Order By: Relevance
“…Different results are consistent with the hypothesis that a key step in the sorting of the chromogranins is their selective, calcium-induced and low pH-induced aggregation in the trans-Golgi network, resulting in the formation of dense cores that exclude constitutive secretory proteins (Huttner et al, 1991). Previously, in our laboratory (Galindo et al, 1991), we reported results indicating (a) that in chromaffin cells, the biosynthesis of chromogranins is not closely linked to the secretory activity and (b) that the biosynthesis of CGA and CGB in chromaffin granules is independently regulated. The relative distribution of CGA and CGB in different species and the different degrees of processing suggest that the two proteins are each regulated by specific mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…Different results are consistent with the hypothesis that a key step in the sorting of the chromogranins is their selective, calcium-induced and low pH-induced aggregation in the trans-Golgi network, resulting in the formation of dense cores that exclude constitutive secretory proteins (Huttner et al, 1991). Previously, in our laboratory (Galindo et al, 1991), we reported results indicating (a) that in chromaffin cells, the biosynthesis of chromogranins is not closely linked to the secretory activity and (b) that the biosynthesis of CGA and CGB in chromaffin granules is independently regulated. The relative distribution of CGA and CGB in different species and the different degrees of processing suggest that the two proteins are each regulated by specific mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…Chromaffin cells (2×10 8 ) were isolated from fresh bovine adrenal glands, cultured as previously reported (18), and plated at a density of 10 7 cells/100 mm in plastic Petri dishes. After 3 days in culture, cells were washed four times with Locke's solution (140 mM NaCl, 4.7 mM KCl, 1.2 mM MgSO 4 , 2.5 mM CaCl 2 , 11 mM glucose, 0.5 mM ascorbic acid, 15 mM Hepes, pH 7.4) to clean out dead cells or cell debris (19). The extracellular medium of nonstimulated cells was collected and used as a control.…”
Section: Isolation Of Proteins Released From Stimulated Chromaffin Cellsmentioning
confidence: 99%
“…The relative distribution of CGA and CGB in different species and the different degrees of processing suggest that the two proteins are each regulated by specific mechanisms. Previously, in our laboratory (Galindo et al, 1991), we reported results indicating (a) that in chromaffin cells, the biosynthesis of chromogranins is not closely linked to the secretory activity and (b) that the biosynthesis of CGA and CGB in chromaffin granules is independently regulated.…”
Section: Discussionmentioning
confidence: 91%